Resonant soft X-ray scattering - a new probe of charge, spin and orbital ordering in the manganites - Hatton, P; Wilkins, S; Beale, T; Johal, T; Prabhakaran, D; Boothroyd, A (2005)
Soft X-ray resonant diffraction is a new technique pioneered by our group. We have published examples of the huge resonant enhancements of charge and magnetic scattering that can be obtained at the L-edges of 3d transition metal oxides. In this paper we will also show how resonant soft X-ray scattering enables direct observation of orbital ordering. We have studied the low temperature phase of La0.5Sr1.5MnO4 that displays charge, spin and orbital ordering. We have employed resonant soft X-ray scattering at the manganese L edges which provide a direct measurement of the orbital ordering. Energy scans at constant wavevector have been compared to theoretical predictions and show that at all temperatures there are two separate contributions to the observed scattering, direct Goodenough orbital ordering and strong cooperative Jahn-Teller distortions of the Mn3+ ions. Finally, we will show how that the spin and orbital degrees of freedom are strongly correlated in these materials. andCOPY; 2004 Elsevier B.V. All rights reserved.